Practical clinical oncology - Hanna, Louise; Crosby, Tom; Macbeth, Fergus (Cambridge : Cambridge University Press, 2007)
Practical Clinical Oncology is a hands-on review of all aspects of practice in clinical oncology. The introductory section to the book provides background information on the four main treatment modalities - radiotherapy, chemotherapy, hormone therapy and biological therapy - plus research, oncological emergencies and palliative care. Subsequent chapters describe the diagnosis and treatment of all malignancies, based on tumour site or type. Each chapter follows a standard template, making it easier for the readers to locate information quickly; multiple choice questions are also provided to enable the reader to test their knowledge. With an emphasis on practical information which will be useful in day-to-day decision-making and treatment, Practical Clinical Oncology is an invaluable resource on clinical care of the cancer patient for all trainees in clinical oncology, medical oncology, surgical oncology and palliative care, as well as specialist nurses and radiographers.
Machine derived contents note: Table of Contents -- List of contributors -- Preface -- Acknowledgements -- Abbreviations -- 1. Practical issues in cytotoxic chemotherapy usage -- Sian Evans and Philip Savage -- 2. Biological treatments in cancer -- Rachel Jones and Robert Leonard -- 3. Hormones in cancer -- Jacinta Abraham and John Staffurth -- 4. Radiotherapy planning -- Andrew Tyler and Louise Hanna -- 5. Research in cancer -- Robert Hills -- 6. Oncological emergencies -- Paul Shaw -- 7. Palliative care -- Simon Noble -- 8. Head and neck -- Laura Moss and Chris Gaffney -- 9. Oesophagus -- Tom Crosby -- 10. Stomach -- Michael Button and Tom Crosby -- 11. Liver, gallbladder and biliary tract -- Somnath Mukherjee and Tom Crosby -- 12. Exocrine pancreas -- Somnath Mukherjee and Tom Crosby -- 13. Colon and rectum -- Richard Adams, Timothy Maughan and Tom Crosby -- 14. Anus -- Richard Adams and Tom Crosby -- 15. Gastrointestinal stromal tumours -- Kate Parker and Tom Crosby -- 16. Breast -- Nayyer Iqbal and Peter Barrett-Lee -- 17. Kidney -- Jason Lester and John Wagstaff -- 18. Bladder -- Stephen Williams and Jim Barber -- 19. Prostate -- Jim Barber and John Staffurth -- 20. Testis -- Jim Barber and John Staffurth -- 21. Penis -- Jim Barber -- 22. Ovary -- Louise Hanna and Malcolm Adams -- 23. Body of the uterus -- Louise Hanna and Malcolm Adams -- 24. Cervix -- Louise Hanna and Malcolm Adams -- 25. Vagina -- Louise Hanna and Malcolm Adams -- 26. Vulva -- Louise Hanna and Malcolm Adams -- 27. Gestational trophoblast tumours -- Philip Savage -- 28. Lung -- Fergus Macbeth and Carys Morgan -- 29. Mesothelioma -- Louise Hanna and Fergus Macbeth -- 30. Soft tissue and bone tumours in adults -- Owen Tilsley -- 31. Haematological malignancies -- Eve Gallop-Evans and Chris Poynton -- 32. Central nervous system -- Sean Elyan -- 33. Skin cancer other than melanoma -- Sankha Suvra Mitra -- 34. Melanoma -- Tom Crosby, Louise Hanna and Dafydd Roberts -- 35. Thyroid -- Laura Moss -- 36. Neuroendocrine tumours -- Atul Kalhan and Aled Rees -- 37. Cancer in children -- Sally Goodman -- 38. Cancer of unknown primary -- Paul Shaw and Tom Crosby -- 39. The use of radiotherapy in the treatment of benign conditions -- Alison Brewster -- Multiple choice questions -- Multiple choice answers -- Index.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Oncology; Cancer